2004
DOI: 10.1152/japplphysiol.01321.2003
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle oxidative metabolism in sedentary humans: 31P-MRS assessment of O2 supply and demand limitations

Abstract: [2013][2014][2015][2016][2017][2018] 1999. To further elucidate these population-specific limitations to metabolic rate, we used 31 P-magnetic resonance spectroscopy to study the exercising human gastrocnemius muscle under conditions of varied FI O 2 in sedentary subjects. To test the hypothesis that PCr recovery from submaximal exercise in sedentary subjects is not limited by O 2 availability, but rather by their mitochondrial capacity, six sedentary subjects performed three bouts of 6-min steady-state submax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 29 publications
8
73
1
Order By: Relevance
“…2). These results are consistent with the unaltered postexercise PCr recovery kinetics (Haseler et al 2004) and leg VO 2max (Cardus et al 1998) in hyperoxia compared to normoxia previously reported in young sedentary subjects and extend these findings to the elderly. These findings, therefore, reveal that the maximal rate of mitochondrial ATP synthesis in the calf muscle is determined by mitochondrial capacity rather than O 2 supply in both young and elderly sedentary individuals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…2). These results are consistent with the unaltered postexercise PCr recovery kinetics (Haseler et al 2004) and leg VO 2max (Cardus et al 1998) in hyperoxia compared to normoxia previously reported in young sedentary subjects and extend these findings to the elderly. These findings, therefore, reveal that the maximal rate of mitochondrial ATP synthesis in the calf muscle is determined by mitochondrial capacity rather than O 2 supply in both young and elderly sedentary individuals.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Pedersen et al (1999) reported diminished leg blood flow and a trend for a lower maximal O 2 consumption during one-leg knee extension exercise in hyperoxia compared to normoxia (Pedersen et al 1999). Interestingly, similar to the present study, Haseler et al (2004) also reported a slight increase in the PCr recovery time constant in hyperoxia compared to normoxia in young untrained individuals, although this difference was less marked (Haseler et al 2004). It cannot be ruled out that breathing hyperoxic gas mixture during our plantar flexion exercise may have resulted in hyperoxic vasoconstriction, thus compromising to some extent O 2 availability in the young untrained subjects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is upon the later unanswered question that we now focus our experiments to initially provide a benchmark for the normal healthy balance between O 2 supply and demand in ambient O 2 in untrained skeletal muscle and ultimately better understand the numerous pathologies that alter O 2 availability and metabolism either individually or in unison. Unlike maximal exercise, an advantage of assessing maximal muscle oxidative metabolism by PCr recovery from submaximal exercise is the low level of stress involved, making it suitable for studying oxidative rate during exercise under conditions of severe hypoxia, and in subjects who are unaccustomed to strenuous exercise due to inactivity, aging, or debilitating pathologies (10,14,18).Consequently, we sought to identify the critical Sa O 2 below which maximal oxidative rate would be reduced in sedentary humans by using arterial oximetry, serial reductions in O 2 availability from normoxia (FI O 2 ϭ 0.21, 0.15, 0.12, and 0.1), and 31 P magnetic resonance spectroscopy (MRS) to measure PCr recovery from plantar flexion exercise. The specific hypothesis tested was that metabolic capacity in untrained human skeletal muscle is perfectly matched to ambient O 2 availability, and hence even a modest reduction in Sa O 2 will significantly impact the maximal mitochondrial oxidative rate, as measured by PCr recovery.…”
mentioning
confidence: 99%
“…It is upon the later unanswered question that we now focus our experiments to initially provide a benchmark for the normal healthy balance between O 2 supply and demand in ambient O 2 in untrained skeletal muscle and ultimately better understand the numerous pathologies that alter O 2 availability and metabolism either individually or in unison. Unlike maximal exercise, an advantage of assessing maximal muscle oxidative metabolism by PCr recovery from submaximal exercise is the low level of stress involved, making it suitable for studying oxidative rate during exercise under conditions of severe hypoxia, and in subjects who are unaccustomed to strenuous exercise due to inactivity, aging, or debilitating pathologies (10,14,18).…”
mentioning
confidence: 99%